Clinical experience with two frameless stereotactic radiosurgery (fSRS) systems using optical surface imaging for motion monitoring. (8th July 2015) - Li, Guang; Ballangrud, Ase; Chan, Maria; Ma, Ruimei; Beal, Kathryn; Yamada, Yoshiya; Chan, Timothy; Lee, James; Parhar, Preeti; Mechalakos, James; Hunt, Margie
Abstract : The purpose of this study was to compare two clinical immobilization systems for intracranial frameless stereotactic radiosurgery (fSRS) under the same clinical procedure using cone‐beam computed tomography (CBCT) for setup and video‐based optical surface imaging (OSI) for initial head alignment and intrafractional motion monitoring. A previously established fSRS procedure was applied using two intracranial immobilization systems: PinPoint system (head mold and mouthpiece) and Freedom system (head mold and open face mask). The CBCT was used for patient setup with four degrees of freedom (4DOF), while OSI was used for 6DOF alignment prior to CBCT, post‐CBCT setup verification at all treatment couch angles (zero and nonzero), and intrafractional motion monitoring. Quantitative comparison of the two systems includes residual head rotation, head restriction capacity, and patient setup time in 25 patients (29 lesions) using PinPoint and 8 patients (29 fractions) using Freedom. The maximum possible motion was assessed in nine volunteers with deliberate, forced movement in Freedom system. A consensus‐based comparison of patient comfort level and clinical ease of use is reported. Using OSI‐guided corrections, the maximum residual rotations in all directions were 1.1 ° ± 0.5 ° for PinPoint and 0.6 ° ± 0.3 ° for Freedom. The time spent performing rotation corrections was 5.0 ± 4.1 min by moving the patient with PinPoint and 2.7 ± 1.0 min by adjusting Freedom couch extension. After CBCT, the OSI–CBCT discrepancy due to different anatomic landmarks for alignment was 2.4 ± 1.3 mm using PinPoint and 1.5 ± 0.7 mm using Freedom. Similar results were obtained for setup verification at couch angles ( < 1.5 mm ) and for motion restriction: 0.4 ± 0.3 mm / 0.2 ° ± 0.2 ° in PinPoint and 0.6 ± 0.3 mm / 0.3 ° ± 0.1 ° in Freedom. The maximum range of forced head motion was 2.2 ± 1.0 mm using Freedom. Both intracranial fSRS immobilization systems can restrict head motion within 1.5 mm during treatment as monitored by OSI. Setting a motion threshold for beam‐hold ensures that head motion is constrained within the treatment margin during beam‐on periods. The capability of 6D setup is useful to improve treatment accuracy. Patient comfort and clinical workflow should play a substantial role in system selection, and Freedom system outperforms PinPoint system in these two aspects. PACS number: 87.53.Ly, 87.55.D‐, 87.57.Q‐, 87.6s.L‐, 87.85.gi